3(2x+5)=2(4x-5)3x

Simple and best practice solution for 3(2x+5)=2(4x-5)3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x+5)=2(4x-5)3x equation:


Simplifying
3(2x + 5) = 2(4x + -5) * 3x

Reorder the terms:
3(5 + 2x) = 2(4x + -5) * 3x
(5 * 3 + 2x * 3) = 2(4x + -5) * 3x
(15 + 6x) = 2(4x + -5) * 3x

Reorder the terms:
15 + 6x = 2(-5 + 4x) * 3x

Reorder the terms for easier multiplication:
15 + 6x = 2 * 3x(-5 + 4x)

Multiply 2 * 3
15 + 6x = 6x(-5 + 4x)
15 + 6x = (-5 * 6x + 4x * 6x)
15 + 6x = (-30x + 24x2)

Solving
15 + 6x = -30x + 24x2

Solving for variable 'x'.

Combine like terms: 6x + 30x = 36x
15 + 36x + -24x2 = -30x + 24x2 + 30x + -24x2

Reorder the terms:
15 + 36x + -24x2 = -30x + 30x + 24x2 + -24x2

Combine like terms: -30x + 30x = 0
15 + 36x + -24x2 = 0 + 24x2 + -24x2
15 + 36x + -24x2 = 24x2 + -24x2

Combine like terms: 24x2 + -24x2 = 0
15 + 36x + -24x2 = 0

Factor out the Greatest Common Factor (GCF), '3'.
3(5 + 12x + -8x2) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(5 + 12x + -8x2)' equal to zero and attempt to solve: Simplifying 5 + 12x + -8x2 = 0 Solving 5 + 12x + -8x2 = 0 Begin completing the square. Divide all terms by -8 the coefficient of the squared term: Divide each side by '-8'. -0.625 + -1.5x + x2 = 0 Move the constant term to the right: Add '0.625' to each side of the equation. -0.625 + -1.5x + 0.625 + x2 = 0 + 0.625 Reorder the terms: -0.625 + 0.625 + -1.5x + x2 = 0 + 0.625 Combine like terms: -0.625 + 0.625 = 0.000 0.000 + -1.5x + x2 = 0 + 0.625 -1.5x + x2 = 0 + 0.625 Combine like terms: 0 + 0.625 = 0.625 -1.5x + x2 = 0.625 The x term is -1.5x. Take half its coefficient (-0.75). Square it (0.5625) and add it to both sides. Add '0.5625' to each side of the equation. -1.5x + 0.5625 + x2 = 0.625 + 0.5625 Reorder the terms: 0.5625 + -1.5x + x2 = 0.625 + 0.5625 Combine like terms: 0.625 + 0.5625 = 1.1875 0.5625 + -1.5x + x2 = 1.1875 Factor a perfect square on the left side: (x + -0.75)(x + -0.75) = 1.1875 Calculate the square root of the right side: 1.089724736 Break this problem into two subproblems by setting (x + -0.75) equal to 1.089724736 and -1.089724736.

Subproblem 1

x + -0.75 = 1.089724736 Simplifying x + -0.75 = 1.089724736 Reorder the terms: -0.75 + x = 1.089724736 Solving -0.75 + x = 1.089724736 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.75' to each side of the equation. -0.75 + 0.75 + x = 1.089724736 + 0.75 Combine like terms: -0.75 + 0.75 = 0.00 0.00 + x = 1.089724736 + 0.75 x = 1.089724736 + 0.75 Combine like terms: 1.089724736 + 0.75 = 1.839724736 x = 1.839724736 Simplifying x = 1.839724736

Subproblem 2

x + -0.75 = -1.089724736 Simplifying x + -0.75 = -1.089724736 Reorder the terms: -0.75 + x = -1.089724736 Solving -0.75 + x = -1.089724736 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.75' to each side of the equation. -0.75 + 0.75 + x = -1.089724736 + 0.75 Combine like terms: -0.75 + 0.75 = 0.00 0.00 + x = -1.089724736 + 0.75 x = -1.089724736 + 0.75 Combine like terms: -1.089724736 + 0.75 = -0.339724736 x = -0.339724736 Simplifying x = -0.339724736

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.839724736, -0.339724736}

Solution

x = {1.839724736, -0.339724736}

See similar equations:

| X(x-15)=35 | | 4n+5(7n-3)=9(n-5) | | (6a-4)=(4a+36) | | 6x=7x-9 | | 4x(x+5)-11=4x^2+17x+1 | | 2.3x+6=-4.3x+9 | | 30(x-5)=30 | | 5w+3w=24 | | 5r^2+12z+4=0 | | 2(3h+11)=6h+4 | | 3(2x+5)=-7(3-2x) | | (3e-32)+(e+16)=180 | | 20y+2(5-15y)=0 | | 18(m+6)=15m-6 | | 10x+12y=166 | | 10x-2(x-3)=8(x+1)+9 | | x^2+20x+64=0 | | 4x-2(-5x-6)=138 | | 10x-12y=166 | | -12-12=x | | 100x^2-9=-5 | | 5y-13-2y+8=0 | | p^2-4=-3 | | 7(3n+8)=12n-7 | | 2(4x+5)=2x-8 | | 6(x+8)=5(x-9)+x | | m^2=25 | | -x^2+6x+135=0 | | 3(8a+5)+6(a+8)=33 | | 9e-14=9e-14 | | x^2=7x+44 | | -2=2(x-1)+6x |

Equations solver categories